Imaging in international sporting event: experience from the Birmingham Commonwealth Games 2022. Issue 6 (June 2023) - Pillai, J.K.; Chari, B.; Hegde, G.; Chapman, P.; Halls, M.; Botchu, R.
Abstract : AIM: To explain the design and delivery of diagnostic imaging and image-guided intervention services for an international games. The authors share their experiences from the Birmingham Commonwealth Games 2022. MATERIALS AND METHODS: A retrospective analysis was undertaken of anonymised data from the Zillion, Easyvision (RIS and PACS), and Encounter platforms for image viewing, interpretation and reporting during the Games. The data collected included age and gender, type of sport, nature of the injury, and imaging findings with diagnoses. RESULTS: The number of individuals who had radiological investigations at the Birmingham Commonwealth Games was 518 and the vast majority of them were athletes (90 %). The average age of athletes who had imaging was 28 years and that of non-athletes who accessed imaging services was 46.4 years with male predominance. Magnetic resonance imaging was the most frequently used imaging technique and the lower limb was the most frequently imaged body part. Athletes playing netball and beach volleyball had the highest percentage of injuries. CONCLUSION: The authors share their experience from the Birmingham Commonwealth Games 2022 regarding the nuances and challenges in radiology service provision for an international sports event that would be helpful for musculoskeletal radiologists in the design and delivery of similar international events in the future. Highlights: Musculoskeletal radiology is an integral component of sports medicine. Early diagnosis of musculoskeletal injuries is essential to decrease morbidity. Imaging enables prognostication and management of musculoskeletal injuries.